Project Report on Bandwidth Efficient Video Multiradio Multicellular Wireless Networks - VINAYAK, RAMESHA L, KISHORE KUMAR and PRAMOD K N (2009)
INTERNAL GUIDE:AVAYAMBAL K, MVJCE EXTERNAL GUIDE: SWATHI SHARMA, Sr PROJECT MANAGER HCL INFO SYSTEM LTD
Keywords: Bandwidth Efficient Video Multiradio Multicellular Wireless Networks